Effect of the NU-AGE Diet on Cognitive Functioning in Older Adults: A Randomized Controlled Trial - Marseglia, Anna; Xu, Weili; Fratiglioni, Laura; Fabbri, Cristina; Berendsen, Agnes A. M.; Bialecka-Debek, Agata; Jennings, Amy; Gillings, Rachel; Meunier, Nathalie; Caumon, Elodie; Fairweather-Tait, Susan; Pietruszka, Barbara; et al. (Frontiers in Physiology, 2018)
BACKGROUND―Findings from animal and epidemiological research support the potential neuroprotective benefits from healthy diets. However, to establish diet-neuroprotective causal relations, evidence from dietary intervention studies is needed. NU-AGE is the first multicenter intervention assessing whether a diet targeting health in aging can counteract the age-related physiological changes in different organs, including the brain. In this study, we specifically investigated the effects of NU-AGE’s dietary intervention on age-related cognitive decline. MATERIALS AND METHODS―NU-AGE randomized trial (NCT01754012, clinicaltrials.gov) included 1279 relatively healthy older-adults, aged 65-79 years, from five European centers. Participants were randomly allocated into two groups: “control” (n=638), following a habitual diet; and, “intervention” (n=641), given individually tailored dietary advice (NU-AGE diet). Adherence to the NU-AGE diet was measured over follow-up, and categorized into tertiles (low, moderate, high). Cognitive function was ascertained at baseline and at one-year follow-up with the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD)-Neuropsychological Battery and five additional domain-specific single cognitive tests. The raw scores from the CERAD subtests (excluding the Mini-Mental State Examination [MMSE)]) and the single tests were standardized into Z-scores. Global cognition (measured with MMSE and CERAD-total score), and five cognitive domains (perceptual speed, executive function, episodic memory, verbal abilities, and constructional praxis) were created. Cognitive changes as a function of the intervention were analyzed with multivariable mixed-effects models. RESULTS―After the one-year follow-up, 571 (89.1%) controls and 573 (89.8%) from the intervention group participated in the post-intervention assessment. Both control and intervention groups showed improvements in global cognition and in all cognitive domains after one year, but differences in cognitive changes between the two groups were not statistically significant. However, participants with higher adherence to the NU-AGE diet showed statistically significant improvements in global cognition (β 0.20 [95%CI 0.004, 0.39], p-value=0.046) and episodic memory (β 0.15 [95%CI 0.02, 0.28], p-value=0.025) after one year, compared to those adults with lower adherence. DISCUSSION―High adherence to the culturally adapted, individually tailored, NU-AGE diet could slow down age-related cognitive decline, helping to prevent cognitive impairment and dementia.